2022
DOI: 10.1007/s40123-021-00427-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Corticosteroid Implantation in Diabetic Macular Edema: Updated European Consensus Guidance on Monitoring and Managing Intraocular Pressure

Abstract: Intravitreal therapy for diabetic macular edema can, in susceptible patients, increase intraocular pressure (IOP). As uncontrolled IOP can potentially be sight threatening, monitoring is an essential component of patient management. It can be challenging for retina specialists to ensure that monitoring is rigorous enough to detect and resolve any potential problems at the earliest opportunity without it also being overburdensome for patients who have the lowest risk of developing an IOP rise. We have developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…13,31 The safety profile of FAc implant should considerer the changes in IOP and the mean time to IOP lowering surgery. 35 No significant changes in IOP were found during follow-up which is in line with other studies. 31,34,36,37 However, SLT was performed in 20.9% of eyes at 36 months post-FAc implant, a higher percentage when compared to other real-word studies.…”
Section: Discussionsupporting
confidence: 91%
“…13,31 The safety profile of FAc implant should considerer the changes in IOP and the mean time to IOP lowering surgery. 35 No significant changes in IOP were found during follow-up which is in line with other studies. 31,34,36,37 However, SLT was performed in 20.9% of eyes at 36 months post-FAc implant, a higher percentage when compared to other real-word studies.…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy of controlling chronic DMO after FAc intravitreal implantation has been widely studied across Europe [ 18 , 29 33 ]. Moreover, international treatment guidelines and consensus on the management of IOP in patients with DMO after FAc intravitreal implantation have been recently published [ 34 , 35 ]. However, few studies other than pivotal reports have focused on its impact on IOP [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Corticosteroid sustained-release agents are also a hot topic in the treatment of DME due to their long duration of maintaining effective drug concentration, simple operation, and reliable efficacy. 11 Boyer et al found that intravitreal injection of dexamethasone, which is a sustained-release agent, can reduce macular oedema and improve patients’ vision. 12 Malcles et al 13 found that implantation of Ozurdex (dexamethasone implant) can improve macular oedema, reduce macular fovea thickness and have good safety in DME patients.…”
Section: Introductionmentioning
confidence: 99%